Politics, religion and political theology - Zank, Michael; Speight, C. Allen (Springer, 2017)
This new volume gives discursive shape to several key facets of the relationship among politics, theology and religious thought. Powerfully relevant to a wealth of further academic disciplines including history, law and the humanities, it sharpens the contours of our understanding in a live and evolving field. It charts the mechanisms by which, contrary to the avowed secularism of many of today’s polities, theology and religion have often, and sometimes profoundly, shaped political discourse. By augmenting this broader analysis with a selection of authoritative papers focusing on the prominent sub-field of political theology, the anthology offsets a startling academic lacuna. Alongside focused analysis of subjects such as conscience, secularism and religious tolerance, the discussion of political theology examines the tradition’s critical moments, including developments during the post-World War I Weimar republic in Germany and the epistemological imprint the theory has left behind in works by political thinkers influenced by the three major monotheistic traditions